Acid‐modified Halloysite Nanotubes as a Stereoselective Catalyst for Synthesis of 2H‐Chromene Derivatives by the Reaction of Isopulegol with Aldehydes. Issue 18 (23rd July 2018) - Sidorenko, Alexander Yu.; Kravtsova, Anna V.; Aho, Atte; Heinmaa, Ivo; Volcho, Konstantin P.; Salakhutdinov, Nariman F.; Agabekov, Vladimir E.; Yu. Murzin, Dmitry
Abstract: Acid‐modified halloysite nanotubes were used for the first time as a stereoselective catalyst for synthesis of oxygen‐containing heterocycles applying of allyl alcohol (−)‐isopulegol condensation with aldehydes to the octahydro‐2 H ‐chromenol (4 R ‐ and 4 S ‐diastereomers) as an example. The catalysts were characterized by XRF, XRD, N2 ‐adsorption, FTIR with pyridine and MAS NMR methods. A high ratio of 4 R /4 S diastereomers (7.6–14.5) under mild conditions in cyclohexane was considerably exceeding previously reported results. Unprecedented selectivity (79–83 %) to 4 R isomer of thiophenyl‐substituted chromenol exhibiting high analgesic activity was achieved. An increase in stereoselectivity with a decrease in the halloysite drying temperature and catalyst acidity clearly indicates formation of 4 R diastereomer on the weak Brønsted sites. This work is an example that control of the stereoselectivity of acid‐catalyzed organic reactions can be effectively carried out by varying water content on the aluminosilicate surface. Modified halloysite nanotubes can be considered as extremely promising catalysts for stereoselective synthesis of heterocyclic compounds. Abstract : Nanotubes for stereoselective synthesis : Halloysite nanotubes were used for the first time as a catalyst for preparation of heterocycle compounds (octahydro‐2 H ‐chromenols) by condensation of allyl alcohol isopulegol with aldehydes. A very high diastereomer ratio exceeding the previously reported results with 74.8–94.2 % overall selectivity was achieved. A key factor in the stereoselectivity control is the amount of water molecules on the nanotubes surface acting as Brønsted acid sites.